Designing Socially-Aware Persuasive Systems: a Proposed Framework - Espinoza, Geovanna Evelyn Taype; Baranauskas, Maria Cecilia Calani (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2020)
Every designer wants their computer systems design to be used by their target audiences. However, the lack of formal support from the persuasive design approaches often leads their projects to fail. In this work we propose a framework with methods, artifacts, tools and steps as a guide to design persua-sive technologies, drawing on the socially- aware design perspective. A case study briefly presented illustrates the use of the framework. Results suggest potential benefits of the proposed framework.